Acoustic enhancement of diffusion in a porous material. - Haydock, D; Yeomans, J (2003)
Lattice Boltzmann simulations are used to model the enhancement of diffusion which results from Eckart (attenuation driven) acoustic streaming in model porous material. Comparisons are made to Fickian diffusion where no flow is present and the diffusion when a fluid jet is used, which represents a more conventional method of enhancement. We show that streaming can produce a higher diffusion rate for the same average flow velocity and propose that this is the result of the continuation within the material of the driving force that produces the acoustic streaming.